2004
DOI: 10.1038/sj.ejhg.5201248
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate QTL linkage analysis suggests a QTL for platelet count on chromosome 19q

Abstract: Platelet count is a highly heritable trait with genetic factors responsible for around 80% of the phenotypic variance. We measured platelet count longitudinally in 327 monozygotic and 418 dizygotic twin pairs at 12, 14 and 16 years of age. We also performed a genome-wide linkage scan of these twins and their families in an attempt to localize QTLs that influenced variation in platelet concentrations. Suggestive linkage was observed on chromosome 19q13. 13 -19q13.31 at 12 (LOD ¼ 2.12, P ¼ 0.0009), 14 (LOD ¼ 2.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…While we have used a candidate gene approach, systematic, genome-wide searches might uncover loci with stronger effects. Linkage-type studies in mice and humans have detected a series of loci for hematologic indices, [12][13][14][15] with one 15 detecting linkage with MCV near the HMIP locus. High-resolution mapping in heterogeneous stock mice, 16 which has a resolution comparable with linkage disequilibrium mapping studies in humans, found significant peaks at a region The ␤ parameter indicates the strength and direction of HMIP-2 haplotype 2.…”
Section: Resultsmentioning
confidence: 99%
“…While we have used a candidate gene approach, systematic, genome-wide searches might uncover loci with stronger effects. Linkage-type studies in mice and humans have detected a series of loci for hematologic indices, [12][13][14][15] with one 15 detecting linkage with MCV near the HMIP locus. High-resolution mapping in heterogeneous stock mice, 16 which has a resolution comparable with linkage disequilibrium mapping studies in humans, found significant peaks at a region The ␤ parameter indicates the strength and direction of HMIP-2 haplotype 2.…”
Section: Resultsmentioning
confidence: 99%
“…However, in the multivariate setting the situation is not so simple de Andrade et al 1997;Amos et al 2001;Marlow et al 2003;Evans et al 2004). The explanation revolves around the fact that a constant component of a random vector not only has zero variance, but also has zero covariance with every other component.…”
Section: Hypothesis Testing and Model Discriminationmentioning
confidence: 99%
“…Eaves et al (1996) extend these ideas to path models that include a QTL source of variation for the study of siblings. Marlow et al (2003) and Evans et al (2004) deftly employ these models on dyslexia-related variables and longitudinal platelet counts. We would also like to call attention to the earlier work on the EM algorithm for multivariate traits by Iturria & Blangero, (2000) as well as work comparing existing computer algorithms for single trait analysis by de Andrade et al (1999).…”
Section: Introductionmentioning
confidence: 99%
“…, where t 1 is a column t-vector of ones (Evans, Zhu et al 2004). This kind of constraint may be reasonable for repeated measures if we believe the gene will have the same effect on all measurements.…”
Section: Multivariate Variance Component Linkage Analysis Some Model mentioning
confidence: 99%
“…This model has a particularly complex asymptotic distribution. The general consensus seems to be that "this issue warrants further detailed attention" (Marlow, Fisher et al 2003), and, "there is an urgent need to characterize the asymptotic distribution associated with these multivariate tests" (Evans, Zhu et al 2004). In a recent paper, Han and Chang (2008) have challenged the correctness of several relevant results in the literature.…”
Section: Introductionmentioning
confidence: 99%